Controlling vibration propagation in a thin beam using a neutraliser - Carneiro, Jean P. [UNESP]; Brennan, Michael J. [UNESP]; Gonçalves, Paulo J.P. [UNESP]; Sorokin, Vladislav S.; Cleante, Vinicius G.; Mace, Brian R. (Elsevier, 2025)
This paper is concerned with the control of vibration transmission along a thin beam using a vibration neutraliser. The analysis focuses on the case where the position of the neutraliser is constrained such that it cannot be at the source or the receiver, and the frequency is sufficiently high so that the evanescent waves are localised near the discontinuities, such as the neutraliser, the excitation point and each end of the beam. The neutraliser, which may be of the translational or rotational type, creates a dip in the displacement transmissibility, which corresponds to an anti-resonance in the transfer receptance between the force source at one end of the beam and the displacement at the other end. It is shown that the frequency at which the dip occurs is not equal to the natural frequency of the neutraliser, which is often the case in many practical situations. It is shown that the frequency at which the dip occurs is dependent only on the local interaction between the neutraliser and the beam, so that the boundary effects of the beam may be neglected. This is demonstrated both analytically and experimentally.
Keywords: Displacement transmissibility; Flexural vibration; Infinite beam; Receptance matrix approach; Semi-infinite beam; Wave transmission